African cassava mosaic disease - Legg, James P. (Elsevier, 2008)
Cassava mosaic disease (CMD), recognized in Africa for more than a century, is now known to be caused by a group of geminiviruses in the genus Begomovirus from the family Geminiviridae. All are transmitted in a persistent manner by the whitefly vector, Bemisia tabaci. Structurally, cassava mosaic geminiviruses (CMGs) are comprised of two small, single-stranded, circular DNA molecules, DNA-A and DNA-B, each of which is encapsidated within a geminate coat. CMG infection results in symptoms comprising misshapen leaves with a mosaic-like chlorosis and general plant stunting, leading to reduced tuberous root production. Through the processes of virus-virus synergism, pseudo-recombination and true recombination, CMGs have evolved into a diverse and highly successful group of plant pathogens and seven species are currently recognized from Africa. Rapid spread of a recombinant strain, East African cassava mosaic virus-Uganda (EACMV-UG), has been associated with a pandemic of unusually severe CMD, which has affected much of East and Central Africa, leading to production losses of 47%, equivalent to nearly 14 million tonnes. Although the deployment of conventionally-bred host plant resistance is the main approach being used to manage CMGs, with considerable success, increased attention is being given to the development of transgenic resistance strategies.